PENGGUNAAN BATANG PISANG KEPOK (Musa paradisiaca formmatypica) DENGAN DOSIS BERBEDA DALAM MENUMBUHKAN PAKAN ALAMI - Natalia Lusia Igo; Ade Yulita Hesti Lukas; Yudiana Jasmanindar (Jurnal Akuakultur Rawa Indonesia, 2020)
This research was conducted for a month, in the laboratory of the Faculty of Marine and Fisheries of Nusa Cendana University. The study aims to determine the use of a banana kepok stem (Musa paradisiaca formmatypica) with different doses to see the type of natural feeds growing and the abundance of it. The banana kepok stem (Musa paradisiaca  formmatypica) generally contains nitrogen, phosphorus and potassium. Nitrogen and phosphorus important to growing of natural feeds, while potassium important to increase the body durability of it. This study uses different dosages to see the abundance of natural feed. The dose used is 50 g.L-1, 75 g.L-1, 100 g. L-1. The results of the study showed the type of natural feed that grows are Daphnia sp and Infusoria and the highest amount of natural feed density in the treatment with dose of 75 g that is Infusoria as much as 356x104 cells.ml-1 and Daphnia sp as much as 168x104 cells.ml-1. The use of stem banana kepok (Musa paradisiaca formmatypica) can be used as feed for fish. Keywords: Banana kepok  stem (Musa paradisiaca formmatypica),  Dosages, Natural feed